Cultivo de microalgas autóctones em efluente de reator anaeróbio : prospecção de cepas e efeito da taxa de diluição na produtividade de biomassa e tratamento terciário - Pereira, Marcos Vinicius Nogueira Lavagnoli (2018)
Effluents from municipal wastewater treatment have been long recognised as suitable media for the cultivation of microalgae biomass. However, few studies report data concerning biomass productivity in continuous reactors using unsterilised wastewater effluents. This study focuses on indigenous microalgae strains that grow with native bacteria and are applicable for biomass production and tertiary wastewater treatment in continuous growth mode. Initially, seven Chlorophyta strains were isolated and grown in batch mode to single out a potential inoculum for the experiments in continuous growth mode. The isolate Chlorella sp. L06 was selected and evaluated based on six dilution rates from 0.1 to 0.6 day-1 on continuous growth reactor using unsterilised secondary effluent as culture medium. Maximal volumetric biomass productivity of 283 mg L-1 day-1 was achieved at 0.3 day-1 without CO2 addition, pH control or air bubbling. Carbohydrates were the major fraction of the dried biomass, followed by proteins and then lipids. The highest removal rates of total nitrogen and phosphorus from the liquid phase were 13.0 and 1.4 mg L-1 day-1 , respectively, and were obtained at 0.4 day-1 . The maximal decay rate for E. coli (2.9 day-1 ) was achieved both at 0.3 and 0.4 day-1 . Conclusively, Chlorella sp. L06 cultivation in unsterilised secondary anaerobic effluent can be adjusted depending on the objective: for biomass production, a dilution rate of approximately 0.3 day-1 is recommended; and for tertiary treatment a rate of 0.4 day-1 is suggested.